Audit report and Statement of accounts of Bangladesh Rural Advancement Committee for the year ended December 31, 1983﻿ - BRAC (© BRAC, 2016)
This Financial Statement prepared by Basu Banerjee & Co. Chartered Accountants, Ispahani Building (5th floor)14 - 15 Motijheel Commercial Area, Dhaka - 2, Bangladesh